Pengintegrasian Perencanaan Sumberdaya Manusia Dan Strategi Organisasional : Catatan Kecil - Palupi, Majang; Tjahjono, Heru Kurnianto (Universitas Muhammadiyah Yogyakarta, 2018)
This study is short review and critical note of author on the article integrating HR planning and organizational strategy written Simon S.K. Lam John Schaubroeck (1998). The author has discussed and written critical note related concepts, practices and methods on their article. Note in this article explained that the integration of human resources planning and organizational strategy play an important role in explaining organizational performance, but contextual aspects should be considered.